Perceived Benefits of Agricultural Lands Offering Agritourism - Barbieri, Carla (2019)
This study investigated residents’ perceived benefits of two types of agricultural lands (farms, cultivated forests) offering agritourism. Specifically, this study compared perceived socio-cultural, environmental, and economic services both types of lands produce and identified socio-economic, lifestyle behavioral, and past visit indicators associated with those perceptions. A survey was mailed to a random sample of 5000 households in Missouri (US), obtaining 969 responses. Respondents perceived that farms and forests produce several socio-cultural, environmental, and economic services to society, with few statistical differences between both. Socio-economic and lifestyle indicators were associated in different ways to residents’ perceptions of the services farms and forests provide. Socializing with friends and visiting those settings during childhood had a positive influence on all types of services derived from both settings. Policy, management, and marketing implications are discussed as to incorporate the benefits agricultural lands provide to society in the planning and development of agritourism.